3(x-3)=-4(5+x)

Simple and best practice solution for 3(x-3)=-4(5+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)=-4(5+x) equation:


Simplifying
3(x + -3) = -4(5 + x)

Reorder the terms:
3(-3 + x) = -4(5 + x)
(-3 * 3 + x * 3) = -4(5 + x)
(-9 + 3x) = -4(5 + x)
-9 + 3x = (5 * -4 + x * -4)
-9 + 3x = (-20 + -4x)

Solving
-9 + 3x = -20 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-9 + 3x + 4x = -20 + -4x + 4x

Combine like terms: 3x + 4x = 7x
-9 + 7x = -20 + -4x + 4x

Combine like terms: -4x + 4x = 0
-9 + 7x = -20 + 0
-9 + 7x = -20

Add '9' to each side of the equation.
-9 + 9 + 7x = -20 + 9

Combine like terms: -9 + 9 = 0
0 + 7x = -20 + 9
7x = -20 + 9

Combine like terms: -20 + 9 = -11
7x = -11

Divide each side by '7'.
x = -1.571428571

Simplifying
x = -1.571428571

See similar equations:

| 8x+4=3x-7 | | 6z=12-42 | | 5x+6-8x-2=19 | | 2n+2=281 | | 9x+9-8x=11 | | 100-5= | | 6x-10=4x-12 | | x/6+(-52)=-84 | | x+18=32 | | -3(2x-3)=19 | | 58x-124=234 | | -5(-4-12n)=-7(1-9n) | | X-6=-5+9 | | y+64=6 | | (x^2-1)-2x^2=0 | | -7y+3=-17 | | 4(y+1)+y=8(y-1)+6 | | 8x-4=6x+10 | | -1+7(12b-5)=11(5+7b) | | -39+t=30 | | -7(1+3x)=-7(x+9) | | 3(9x-1)=-30 | | 9z=12-30 | | x^2-13x-38=0 | | 2/5w-3/2=-7/3 | | 12n3+8x2-6n/2x2 | | 4(v+3)=-5v-33 | | I/(2+I) | | f=9/5c*30+32 | | 6x-16=40 | | 9(-3r-5)=-11(1+4r) | | -28.7=-3.1+u/2 |

Equations solver categories